An investigation of the Presence of aflatoxins in feeds in Greece - ΒΑΣΙΛΟΠΟΥΛΟΣ Β.; ΣΠΑΗΣ Α. Β.; ΚΟΥΦΙΔΗΣ Δ.; ΧΑΤΖΗΓΕΩΡΓΙΟΥ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The great importance of aflatoxins’ toxicity together with the fact that their existence in feeds has not examined intensively in Greece, were the reasons for undertaking this investigation in order to determine whether a potential problem exists and if so, to study the extent of this problem. For that purpose 450 samples, of different kinds of feeds, taken randomly from all over the country between the years 1974 and 1977, were examined. The data obtained can be concerned as encouraging, since only 23 samples (5,11%) were confirmed as positive, and the concentrations of aflatoxins were, most of all, below the European Economic Community tolerances for feeds. Considering that nobody can prejudge the repeatability of these favourable data it is imposed to control continually and systematically the aflatoxin level in feeds and to establish a relative legislation in our country.